2014
DOI: 10.17576/gema-2014-1402-07
|View full text |Cite
|
Sign up to set email alerts
|

The Refugee Swap Deal in Malaysian Online News Reports: Ideology and Representation

Abstract: Using Critical Discourse Analysis, this study attempts to examine the representation of Refugees, Asylum Seekers and Immigrants (henceforth RASIM) in news reports from three selected English online newspapers in Malaysia: The Star, The New Straits Times (NST) and Malaysiakini. This research aims to reveal the representations of RASIM and attempts to unravel the ways in which ideology and context shape the discourse surrounding RASIM. The focus of the article is the Refugee Swap Deal between Australia and Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…It shows a negative image for such as a) Iran is trying to hide information from world' sight, and b) Iran is changeable in its nuclear program. Like to the studies above, Bolte and Keong (2014) analyzed CDA as the ideological representation of illegal immigrants in the Malaysia news that outlines the manner a text is made (Jorgenson & Phillips, 2002;Fairclough, 1992) and vice-versa. It was found in the media discourse is the tools to protect of agreement that denotes a positive representation of Malaysia and Australia.…”
Section: Fairclough's Framework Applicationmentioning
confidence: 99%
“…It shows a negative image for such as a) Iran is trying to hide information from world' sight, and b) Iran is changeable in its nuclear program. Like to the studies above, Bolte and Keong (2014) analyzed CDA as the ideological representation of illegal immigrants in the Malaysia news that outlines the manner a text is made (Jorgenson & Phillips, 2002;Fairclough, 1992) and vice-versa. It was found in the media discourse is the tools to protect of agreement that denotes a positive representation of Malaysia and Australia.…”
Section: Fairclough's Framework Applicationmentioning
confidence: 99%
“…Readers are usually exposed to stories written either from the journalists' or influential people's point of view, and not accounts by the women themselves. This aspect is also apparent in a study on media's representation of refugees, asylum seekers, and immigrants (Bolte & Keong, 2014) which revealed more priority being given to the voices of prominent individuals. Misman, Adnan, Firdaus, and Ahmad (2017), in their study about foreign nationals as offenders and victims, also found an absence of foreigners' voices in the media.…”
Section: Topos Of Victimisationmentioning
confidence: 99%
“…This study exhibits how the media (re) shape public perception, arguably, through the reality they construct in framing groups of people, for instance, protesters vs. authorities. Bolte and Keong (2014) also established that media discourse reflects distinctive information about various discursive strategies upon which media rely to represent issues. Contrary to the framing of the authorities, the Arab Spring protesters were again positively framed as a 'spirit of change' through the lexical choices such as desire for change (NI) and inspiration (AN).…”
Section: Editorial Charges and Endorsementsmentioning
confidence: 99%